Research on Mechanism of Rock Burst in Key Working Faces under Thick Magmatite in Deep Mine - WeiLi Yang; ZhiZeng Zhang; QuanDe Wei; XiaoCheng Qu; JingLin Wen (Shock and Vibration)
The rock burst of key working faces under the thick hard rock in deep mine significantly threatens the mining safety of deep mine. In this study, the key working faces under typical deeply buried thick magmatite were adopted as the engineering background. The mine pressure characteristics during the mining in key working faces under thick magmatite in deep mine were measured and analyzed. Then, the evolution of overburden strata structure under the control of thick magmatite was explored based on the theory of mine pressure to conclude that the horizontal “carrier” load of broken rock beam, the vertical “loader” load, and the shock bump load from thick magmatite fracture are main sources of force behind the burst. Finally, the mechanism of rock burst was studied on the basis of the balanced relationship between loading and bearing. According to the results of research, the burst in key working faces under thick magmatite in deep mine was actually the instability burst of the key working face block. The bearing capacity and load of key working face block were constantly changing during the unstable movement of thick magmatite. The rock burst would occur in the event of any instability during the dynamic confrontation of “loading-bearing”. As per different burst sources, it could be divided into flexural loading burst of thick magmatite and shock bump burst of thick magmatite fracture. The mechanical conditions for each of the two bursts and the width calculation formula for the key working face free from overall instability burst were deduced. The research results were applied to key working face 12310. Meanwhile, the purpose of safe production following the principle of “No disaster in bumps, no harm under burst” was realized by implementing the “Four Keys” comprehensive prevention and control measures of “key monitoring + key speed reduction + key pressure relief + key support”.